2002
DOI: 10.1530/eje.0.1460491
|View full text |Cite
|
Sign up to set email alerts
|

Two novel missense mutations in the thyroid peroxidase gene, R665W and G771R, result in a localization defect and cause congenital hypothyroidism

Abstract: Objective: Thyroid peroxidase (TPO) deficiency is one of the causes of thyroid dyshormonogenesis, because TPO plays a key role in thyroid hormone biosynthesis. To determine the frequency and pattern of TPO abnormalities, we have been screening TPO genes of patients with congenital goitrous hypothyroidism. Subjects and methods: TPO genes of a patient with congenital goitrous hypothyroidism and her parents were directly sequenced, and two novel missense mutations (R665W and G771R) were found. The former was deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 31 publications
5
47
3
Order By: Relevance
“…By immunofluorescence, we observed a defect in the transport of the mutant TPO 766 -775 to the plasma membrane (data not shown). A similar observation was described recently by Umeki et al (51), who showed that when the Gly 771 is replaced by Arg 771 in the TPO genes of patients, this results in a localization defect (accumulation of mutated TPO in the endoplasmic reticulum) and causes congenital hypothyroidism. To overcome this problem, we decided to extract all membrane proteins from wt and stably transfected CHO and to study them by Western blotting and ELISA.…”
Section: Fig 2 Analysis Of T13-specific Mimotopes By the Spot Technsupporting
confidence: 84%
“…By immunofluorescence, we observed a defect in the transport of the mutant TPO 766 -775 to the plasma membrane (data not shown). A similar observation was described recently by Umeki et al (51), who showed that when the Gly 771 is replaced by Arg 771 in the TPO genes of patients, this results in a localization defect (accumulation of mutated TPO in the endoplasmic reticulum) and causes congenital hypothyroidism. To overcome this problem, we decided to extract all membrane proteins from wt and stably transfected CHO and to study them by Western blotting and ELISA.…”
Section: Fig 2 Analysis Of T13-specific Mimotopes By the Spot Technsupporting
confidence: 84%
“…The TPO gene spans over 150 kb on the short arm of chromosome 2, locus 2p25, and consists of 17 exons (9,10). Published molecular genetic studies suggest that TPO gene mutations are one of the most common causes of thyroid dyshormonogenesis, with several different inactivating mutations being identified in patients with total iodide organification defects (TIOD; (7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)). The inheritance is autosomal recessive (16,29).…”
Section: Introductionmentioning
confidence: 99%
“…This amino acid substitution was not identified in 50 healthy controls. Two known different heterozygous polymorphisms were also found:1207 G®T and 1283 C®G in exon 8 [7,8]. The other was a heterozygous 10 base deletion of intron 15-exon 16 boundary (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Approval of the Hokkaido University School of Medicine ethics committee was also received. Genomic DNA was extracted and each exon of the TPO gene was amplified by polymerase-chain-reaction (PCR) using primers according to previous studies in a Perkin-Elmer Gene Amp PCR System 2400 thermal cycler (PE Applied Biosystems, Foster City, CA) [4,7]. After amplification, the purified PCR products were sequenced directly with an ABI PRISM Dye Terminator Cycle Sequencing Kit and an ABI 373A automated fluorescent sequencer (PE Applied Biosystems, Foster City, CA) from both strands.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation